Морфологічні і фізіолого-біохімічні показники посухостійкості Triticum aestivum L. - ОРЛЮК, АНАТОЛІЙ ПАВЛОВИЧ; УСИК, ЛЮДМИЛА ОЛЕКСАНДРІВНА (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Морфологічні і фізіолого-біохімічні показники посухостійкості Triticum aestivum L.